Intraoperative Cone-Beam Computed Tomography Navigation Versus 2-Dimensional Fluoroscopy in Single-Level Lumbar Spinal Fusion: A Comparative Analysis - Gianluca Vadalà; Giuseppe Francesco Papalia; Fabrizio Russo; Paolo Brigato; Luca Ambrosio; Rocco Papalia; Vincenzo Denaro (Neurospine, 2024)
Objective Several studies have advocated for the higher accuracy of transpedicular screw placement under cone-beam computed tomography (CBCT) compared to conventional 2-dimensional (2D) fluoroscopy. The superiority of navigation systems in perioperative and postoperative outcomes remains a topic of debate. This study aimed to compare operative time, screw placement time and accuracy, total radiation dose, perioperative and postoperative outcomes in patients who underwent transpedicular screw fixation for degenerative lumbar spondylolisthesis (DLS) using intraoperative CBCT navigation versus 2D fluoroscopy. Methods A retrospective analysis was conducted on patients affected by single-level DLS who underwent posterior lumbar instrumentation with transpedicular screw fixation using surgical CBCT navigation (NV group) or 2D fluoroscopy-assisted freehand technique (FH group). Demographics, screw placement time and accuracy, operative time, total radiation dose, intraoperative blood loss, screw revision rate, complications, and length of stay (LOS) were assessed. Results The study included a total of 30 patients (NV group: n = 15; FH group: n = 15). The mean screw placement time, operative time, and LOS were significantly reduced in the NV group compared to the FH group (p < 0.05). The total radiation dose was significantly higher in the NV group (p < 0.0001). No significant difference was found in terms of blood loss and postoperative complications. Conclusion This study suggests that intraoperative CBCT-navigated single-level lumbar transpedicular screw fixation is superior in terms of mean screw placement time, operative time, and LOS compared to 2D fluoroscopy, despite a higher intraoperative radiation exposure.